2011
DOI: 10.1152/ajpheart.00232.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic skeletal muscle ischemia preserves coronary flow in the ischemic rat heart

Abstract: Varnavas VC, Kontaras K, Glava C, Maniotis CD, Koutouzis M, Baltogiannis GG, Papalois A, Kolettis TM, Kyriakides ZS. Chronic skeletal muscle ischemia preserves coronary flow in the ischemic rat heart. Am J Physiol Heart Circ Physiol 301: H1229-H1235, 2011. First published July 15, 2011; doi:10.1152/ajpheart.00232.2011.-Chronic skeletal muscle ischemia confers cytoprotection to the ventricular myocardium during infarction, but the underlying mechanisms remain unclear. Although neovascularization in the left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…For example, a brief pre-MI ischemic insult of skeletal muscle is reported to decrease infarct size434445 and chronic ischemia of skeletal muscle can increase left ventricle coronary vessel density46. These results suggest that ischemic muscle may exert its cardioprotection through some neurohumoral mechanism47.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a brief pre-MI ischemic insult of skeletal muscle is reported to decrease infarct size434445 and chronic ischemia of skeletal muscle can increase left ventricle coronary vessel density46. These results suggest that ischemic muscle may exert its cardioprotection through some neurohumoral mechanism47.…”
Section: Discussionmentioning
confidence: 99%
“…The low dosage of this anaesthetic protocol, coupled with its brief duration associated with the ex vivo experimental conditions, precludes significant effects on cardiac function. After a left lateral thoracotomy, the hearts were rapidly excised and were mounted on a Langendorff apparatus (ML870B2 system, ADInstruments, Oxfordshire, UK), as previously described [27, 33]. The preparations were perfused at a constant flow of 12.5 ml/min with Krebs-Henseleit solution at the following composition (in mmol/L): NaCl: 118.1, KCl: 4.6, CaCl 2 : 2.5, MgSO 4 : 1.2, KH 2 PO 4 : 1.2, NaHCO 3 : 24.8, and glucose: 10.33.…”
Section: Methodsmentioning
confidence: 99%
“…The pH and temperature were kept stable at 7.4 and 37°C, respectively. To ensure comparable measurements, atrial pacing was performed at a rate of 300 beats per minute during the stabilization period and during reperfusion; as in previous reports, pacing was continued during regional [34], but not during global [27, 33] ischaemia. …”
Section: Methodsmentioning
confidence: 99%
“…Unlike IPC, PRIT has a more remote effect by facilitating coronary collateral formation of the myocardium by repeated short-term skeletal muscle ischemia. The cardioprotective effect of short-term skeletal muscle ischemia has been previously evaluated in experimental [20] and clinical [21] studies and the beneficial effect on the ventricular myocardium is not specific for a particular species [8]. PRIT is reversible non-invasive ischemia of normal skeletal muscles caused by tourniquet or isometric contraction, induce collateral circulation development in the myocardium (9).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that remote ischemic preconditioning (RIPC) could overcome the aforementioned problem associated with IPC in that and it was still cardioprotective when applied to an organ or tissue away from the heart [7]. Further research demonstrated that remote muscle trainings could facilitate coronary collateral circulation formation, and therefore more attention has been paid to such trainings because they are easily accessible and can be manipulated without major risks in the clinical setting, should this method prove to be of therapeutic value [8]. Exercise training does not seem to accelerate the development of coronary collaterals with normal coronary arteries.…”
Section: Introductionmentioning
confidence: 99%